PENYELESAIAN SENGKETA DALAM KASUS SANDA PADA MASYARAKAT BANJAR - Muhamad Rahmani Abduh; H.M. Hanafiah (Pascasarjana UIN ANTASARI Banjarmasin, 2021)
AbstractThis research is motivated by sanda transactions carried out by the Banjar community which are not free from disputes. This study aims to find out how the types of disputes that occur in sanda transactions are and how the settlement mechanism is. The method used in this research is descriptive method. The results of this study indicate that there are three cases of dispute in the sanda transaction, namely; disputes due to the party